The acute effects of exercise on cortical excitation and psychosocial outcomes in men treated for prostate cancer: a randomized controlled trial - Santa Mina, Daniel; Guglietti, Crissa L.; de Jesus, Danilo R.; Azargive, Saam; Matthew, Andrew G.; Alibhai, Shabbir M. H.; Trachtenberg, John; Daskalakis, Jeffrey Z.; Ritvo, Paul (Frontiers in Aging Neuroscience, 2014)
Purpose: Regular exercise improves psychological wellbeing in men treated for prostate cancer. For this population and among cancer survivors in general, the effect of a single bout of exercise on self-report or objective measures of psychological wellbeing has not been examined. We examined the acute effect of a single bout of exercise on the cortical silent period (CSP) and on self-reported mood in men that have received treatment for prostate cancer. Methods: Thirty-six prostate cancer survivors were randomly assigned to 60 minutes of low to moderate intensity exercise or to a control condition. Outcomes were assessed immediately before and after either the exercise or the control condition. Results: No significant differences in baseline CSP or mood were observed following the exercise session or control conditions. Participants with higher scores of trait anxiety had significantly shorter CSP at baseline, as well as those receiving androgen deprivation therapy. Age and baseline CSP had a low-moderate, but significant negative correlation. Changes in CSP following the exercise condition were strongly negatively correlated with changes in self-reported vigor. Conclusions: While we did not observe any acute effect of exercise on the CSP in this population, the associations between CSP and trait anxiety, age, and vigor are novel findings requiring further examination. Implications for Cancer Survivors: Exercise did not acutely affect our participants in measures of psychological wellbeing. Additional mechanisms to explain the chronic psychosocial benefits of exercise previously observed in men with prostate cancer require further exploration. Clinicaltrials.gov Identifier: NCT01715064 (http://clinicaltrials.gov/show/NCT01715064)